Social marketing vs commercial marketing: something in common for gains / Mazlan Che Soh - Che Soh, Mazlan (Faculty of Administrative Science and Policy Studies, 2012)
Social marketing is a distinct marketing discipline and it was first coined formally 41 years ago by Philip Kotler and Gerald Zaltman, based from a pioneering article in the Journal of Marketing by Kotler and Levy in 1969. These articles describe “the use of marketing principles and techniques to advance a social cause, idea or behavior”. Indeed, social marketing shares much in common with marketing in the business world. In business marketing, sellers dispatch goods, services, and communications (e.g. advertising) to the market and in return, money (consumer purchases), information (consumer research), and customer loyalty are received. However in social marketing more concern with the principles and techniques to create, communicate and deliver value in order to influence target audience behaviors that benefit society (public health, safety, the environment, and communities) as well as the target audience (Kotler, Lee and Rotschild, 2006). On the other note, social marketing is more concern with “influencing public behavior”. Many concepts and tools are shared by marketing goods and services and social marketing. This conceptual paper explores the relationship and benefits gained by those who know the application.